Stress Corrosion Cracking Analysis of the ER70S Wire and SS400 Steel Plate Joints - Darmadi, Djarot B.; Andika Dewa Satrio; Slamet Prasetyo Utomo (International Journal of Integrated Engineering, 2024)
The susceptibility of weld joints to the Stress Corrosion Cracking (SCC) load alarmed the researchers since pipeline blow-out which were initiated in the area closed to the weld joints. This article is evaluating the SCC resilience of the ER70S wire filler metal to the SS400 plate. The Capacitive Discharge Welding (CDW) with varied angle of the filler metal as an independent variable, whilst the other parameters were kept constant. The joint, then exposed to the SCC load, i.e., dipped in the 1M HCl solution with varied external tensile load to obtain the dependent variable: time to failure (time to brake). The results show that, generally, a sharper wire tip provides higher SCC resilience accept what was shown by the 30? specimen. With the sharper wire tip, the higher volume of weld nugget is provided which guarantee the enough number of weld metal. However, the impact phenomenon in the CDW process splashed this too much nugget beyond the formed joint which is proven by the many spatters in the weld joint. This thrown out nugget substance in turn decrease the intended nugget volume to form the joint. The results show the 60? wire tip angle provide the joint with the highest SCC resilience, indicated by the longest time to brake when loaded with an equal external load